Density‐mediated indirect effects from active predators and narrow habitat domain prey. Issue 10 (22nd August 2017) - Rinehart, S. A.; Schroeter, S. C.; Long, J. D.
Abstract: The hunting‐mode–habitat‐domain‐range framework suggests that the mechanism driving trophic cascades (i.e., trait‐mediated indirect interactions [TMIIs] vs. density‐mediated indirect interactions [DMIIs]) should depend upon the functional traits of predators and prey. For example, trophic cascades containing active, broad habitat domain range (BHDR) predators interacting with narrow habitat domain range (NHDR) prey are predicted to arise primarily via TMIIs, because these prey should reduce their conspicuous activity in the presence of these predators. Unfortunately, this hypothesis is difficult to test given the strong bias against studies assessing trophic cascades containing NHDR prey. Furthermore, this hypothesis ignores evidence that (1) active predators can have high consumption rates on prey, (2) continuously responding to active predators foraging across broad areas is energetically costly for prey, and (3) cues from active, BHDR predators may not influence prey density. We examined the TMIIs and total indirect interaction (TII) produced during interactions between an active, BHDR ladybeetle predator ( Naemia seriata ) and its NHDR prey (scale insects). We exposed scale insects to nonlethal and lethal ladybeetle predators in laboratory mesocosms for 15 weeks. We measured the growth of the scale insect's host plant (cordgrass) and the population density of scale insects. Contrary to theory, nonlethal ladybeetles did not induce TMIIs. However, lethal ladybeetles increased cordgrass total and root dry biomass by 36% and 44%, respectively, suggesting the presence of strong DMIIs. Additionally, both lethal and nonlethal ladybeetles reduced scale insect population density. Our findings suggest that DMIIs, rather than TMIIs, can result from interactions between active BHDR predators and NHDR prey.